Implementasi Literasi Digital Pada Mata Pelajaran Ipas Sekolah Dasar - Wendi Nilpa Apriana; Ade Susanti (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
This research aims to obtain information regarding the role of digital literacy for students, especially in the learning and teaching process of science and science subjects in elementary schools. In science and science learning, digital literacy has a very important role because it prepares students who are qualified, reliable and able to compete internationally. To be able to create and develop digital literacy in science and science learning, teachers need to create learning conditions that involve active students. The aim of this research is to determine the implementation of digital literacy in science and science learning in elementary schools. The methods used in this research are literature review/literature study and field observations and interviews. Data was obtained from reviewing articles, journals and other sources related to research and also through observations and interviews and then concluded. Data processing and analysis was carried out qualitatively with descriptive explanation. It is known from the results of this research that the implementation of digital literacy can help students and teachers in implementing the independent curriculum and strengthening the profile of Pancasila students in elementary school.